Ammonia flux tailoring on the quality of AlN epilayers grown by pulsed atomic-layer epitaxy techniques on (0 0 0 1)-oriented sapphire substrates via MOCVD. Issue 12 (6th March 2019) - Abd Rahman, Mohd Nazri; Talik, Noor Azrina; Abdul Khudus, Muhammad I. M.; Sulaiman, Abdullah Fadil; Allif, Kamarul; Zahir, Norhilmi Mohd; Shuhaimi, Ahmad
Abstract : A smooth and dense single-crystalline AlN was successfully grown by tailoring the flux density of ammonia. Abstract : A smooth and dense surface of single-crystalline aluminium nitride thin films has been epitaxially grown on (0 0 0 1)-sapphire substrates by tailoring and optimizing the ammonia flux density during deposition. The aluminium nitride films were deposited by metal organic chemical vapour deposition using the pulsed atomic-layer epitaxy technique at a relatively low growth temperature for ammonia flux densities between 2.2 and 0.2 standard litres per minute (SLM). It is found that the ammonia flux of 0.6 SLM produced the best quality of aluminium nitride films. Field emission scanning electron microscopy as well as atomic force microscopy images revealed a smooth, crack-free and dense surface of aluminium nitride films with the lowest root mean square roughness of 1.61 nm. The in-plane compressive strain inside aluminium nitride films, induced by the hetero-epitaxial growth on sapphire, was examined by focusing on the transition of the E2 (high) peak frequency obtained from the Raman spectra. The lowest threading and mixed-edge dislocation densities were estimated to be 1.50 × 10 7 and 3.7 × 10 9 cm −2, respectively, which are comparable to those of state-of-the-art aluminium nitride thin films.